Corynebacterium spp.: Underestimated Pathogens with High Virulence Potential - E. O. Mangutov; G. G. Kharseeva; V. N. Gerasimov; A. A. Alieva; N. A. Voronina; E. L. Alutina; V. P. Slukin; O. E. Khokhlova; A. R. Gaitrafimova; N. K. Fursova (Эпидемиология и вакцинопрофилактика)
Relevance. Corynebacterium spp., being opportunistic microorganisms, play a role in the development of inflammatory diseases of various localization, including HCAI. Possessing multiple resistance to AMP and pathogenic properties, they cause infections that are not controlled by means of vaccine prophylaxis. The aim of the study was to evaluate the prevalence and virulent properties of Corynebacterium spp. strains isolated from patients with inflammatory diseases of the respiratory tract. Materials and methods. Strains of Corynebacterium spp. isolated from the pharynx and nose of patients with inflammatory diseases of the respiratory tract (99 pcs.) and practically healthy individuals (33 pcs.) at 2017–2021 in Rostov-on-Don. The ultrastructure of corynebacteria was studied using a TecnaiG2 Spirit BioTWIN transmission electron microscope (FEI, Czech Republic); cytopathic effect (CPE) on CHO-K1 cell culture; virulence in the larval model of the wax moth Galleria mellonella. Results and discussion. The species diversity of Corynebacterium spp. strains isolated from patients is much wider than in the examination of practically healthy individuals (16 and 6 species of Corynebacterium, respectively). An electron microscopic study revealed morphological features of the cell ultrastructure of various strains of Corynebacterium spp., possibly associated with their ability to damage. The strains of C. striatum, C. aurimucosum, C. coyleae, C. falsenii, C. argentoratense, C. afermentans, C. amycolatum, C. freneyi, C. simulans isolated from patients had the highest level of CPЕ. Corynebacterium spp. strains isolated from patients had different levels of virulence against G. mellonella larvae. This testified to the importance of establishing not so much the species as the strain of these microorganisms. Conclusion. A wide species diversity of strains of Corynebacterium spp., isolated from patients with inflammatory diseases of the respiratory tract, mainly of childhood, was found. The most frequently isolated species were C. pseudodiphtheriticum, C. propinquum and C. accolens. Strains of Corynebacterium spp., isolated from patients, were mainly characterized by a high level of cytotoxicity and virulence, which indicates their role in the development of the infectious process.